Semaphorins and their receptors in pancreatic cancer: Mechanisms and therapeutic opportunities - Liu, Dahai; Li, Jie; Qi, Fei; You, Hua (Frontiers in Oncology, 2023)
Pancreatic cancer (PC) is a malignant tumor with high malignancy that is difficult to diagnose and treat. PC is a major medical problem because of its low early diagnosis rate, high surgical mortality rate, low cure rate, and expensive related testing cost. Therefore, the significance of finding new markers for PC is self-evident. Semaphorins (Semas) have been shown to affect angiogenesis and lymphangiogenesis and can also directly affect the behavior of tumor cells. The expression and related action targets of its family members on PC are summarized in this review.